Nutritional management for a lung cancer patient receiving concurrent radiotherapy and immunotherapy and developing immune-related dermatitis: a case report - Zeng, Yanlin; Zhang, Xinmei; Qin, Di; Zhong, Yanping; Wei, Bihong; Liang, Jun (Frontiers in Nutrition, 2025)
IntroductionConcurrent radiotherapy and immunotherapy is an alternative treatment regimen for elderly patients with locally advanced non-small cell lung cancer (NSCLC) who have contraindications to or decline surgery and chemotherapy. While these patients are susceptible to malnutrition and treatment-related adverse events, experience for their nutritional management is still lacking. In this case report, we summarized the nutritional management process for a NSCLC patient with severe malnutrition, who received concurrent radiotherapy and immunotherapy and developed immune-related dermatitis.Case summaryIn March 2024, a 71-year-old male with lung squamous cell carcinoma and severe malnutrition was hospitalized in Cancer Hospital Chinese Academy of Medical Sciences, Shenzhen Center. During concurrent radiotherapy and tislelizumab immunotherapy, the patient developed grade 2 radiation-induced esophagitis and grade 3 immune-related dermatitis. The medical team dynamically assessed the patient’s nutritional status, set reasonable nutritional goals, and promptly adjusted nutritional prescriptions according to the severity and cause of the nutritional gap. Key measures included upgrading to combined enteral and parenteral nutrition support during radiation-induced esophagitis complicated by immune-related oral ulcers, adjusting the type of parenteral nutrition formulation for suspected lipid emulsion allergy, and strengthening immunonutrient supplementation during the dermatitis phase. Concurrently, progressive aerobic and resistance exercise training was guided to promote rehabilitation. Via the phased nutritional management, the patient’s nutritional indicators significantly improved after 54 days of hospitalization. Anti-tumor treatment was successfully completed, and the dermatitis healed.ConclusionFor lung cancer patients complicated with immune-related dermatitis during concurrent radiotherapy and immunotherapy, whole-course management including phased adjustment of nutritional strategies, early differentiation of dermatitis, and integration with exercise rehabilitation may effectively improve nutritional status and promote dermatitis healing, thus supporting the completion of anti-cancer therapy. Further studies with larger sample sizes are required to confirm the effect of nutritional management.